2019
DOI: 10.18502/ijrm.v17i2.3985
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of vitamin E on rats’ ovarian follicles following an administration of diazinon: An experimental study

Abstract: follicles following an administration of diazinon.Materials and Methods: A total of 30 adult female Wistar rats were divided into fivegroups: a control group (without any intervention), sham group (received only pureolive oil, as solvent), experimental group I (DZN+olive oil, 60 mg/kg), experimentalgroup II (vitamin E, 200 mg/kg), and experimental group III (DZN: 60 mg/kg+vitaminE: 200 mg/kg). All drugs were injected intraperitoneally, except vitamin E which wasadministrated by gavage. The animals were scarifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…This structural change is caused by its reactive metabolite, free radicals diazoxon, which causes structural damage and disruption of cell membrane function, even cell death. 1,3,19 The results of this study are in line with previous researches showing a change in liver histopathology, such as sinusoid dilatation, narrowed central veins, parenchymal degeneration, hydropic degeneration, fatty degeneration, and necrosis. 1,20 Sinusoid dilatation in this study is in line with studies conducted by Al-Attar (2014) and Marzano et al (2015), which occurs due to pressure on the cell walls due to containment of the veins by toxic substances.…”
Section: Resultssupporting
confidence: 91%
“…This structural change is caused by its reactive metabolite, free radicals diazoxon, which causes structural damage and disruption of cell membrane function, even cell death. 1,3,19 The results of this study are in line with previous researches showing a change in liver histopathology, such as sinusoid dilatation, narrowed central veins, parenchymal degeneration, hydropic degeneration, fatty degeneration, and necrosis. 1,20 Sinusoid dilatation in this study is in line with studies conducted by Al-Attar (2014) and Marzano et al (2015), which occurs due to pressure on the cell walls due to containment of the veins by toxic substances.…”
Section: Resultssupporting
confidence: 91%
“…A clinical study found that VE combined with selenium supplementation significantly improved AMH index, antral follicle count (AFC) and mean ovarian volume (MOV) in patients with occult POI [227]. Experimental studies have found that VE intervention can enhance the antioxidant capacity of ovarian tissue, regulate endocrine hormones, reverse follicular atresia, and restore the normal vascular distribution of ovarian tissue [228]. VE was also shown to be involved in the normal antioxidant function of GSH-Px1 as an essential cofactor [229].…”
Section: Vitaminsmentioning
confidence: 99%
“…The most important action of DZN compound toxicity is the inhibition of ChE activity and the accumulation of ACh in the peripheral and central nervous system leading to increased activation of nicotinic and muscarinic receptors [28].…”
Section: Effects Of Treatments On Che and Antioxidant Enzymes Activitiesmentioning
confidence: 99%